Remote and precise control over morphology and motion of organic crystals by using magnetic field - Li, Liang (2022)
Elastic organic crystals are the materials foundation of future lightweight flexible electronic, optical and sensing devices, yet precise control over their deformation has not been accomplished. Here, we report a general non-destructive approach to remote bending of organic crystals. Flexible organic crystals are coupled to magnetic nanoparticles to prepare hybrid actuating elements whose shape can be arbitrarily and precisely controlled simply by using magnetic field. The crystals are mechanically and chemically robust, and can be flexed precisely to a predetermined curvature with complete retention of their macroscopic integrity at least several thousand times in contactless mode, in air or in a liquid medium. These crystals are used as optical waveguides whose light output can be precisely and remotely controlled by using a permanent magnet. This approach expands the range of applications of flexible organic crystals beyond the known limitations with other methods for control of their shape, and opens prospects for their direct implementation in flexible devices such as sensors, emitters, and other (opto)electronics.